THE REFLECTION OF FRENCH CULTURE IN LITERARY TEXTS (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The article is devoted to investigation of reflection of French culture in literary texts. A major part of the culture is language and literature. Knowledge of a foreign language and foreign literature is of great importance in the upbringing of a harmonious generation in today's education. Learning a foreign language is undoubtedly associated with foreign literature. Foreign literature provides the basis for the upbringing of the younger generation and the ability of young people to have a quality knowledge base. Foreign literature allows you to study a foreign language, its culture, national traditions and values. major part of the culture is language and literature.